Loss of innocence - Patterson, Richard North (Quercus, 2013)
A family drama of dark secrets and individual awakenings is set against the backdrop of the turbulent summer of 1968 in Martha's Vineyard, where twenty-two-year-old Whitney Dane begins questioning her goals and sense of independence at the side of a fiercely ambitious, underprivileged man.